“Floc” Contribution to Peneid Intensive Culture - Cuzon, G.; Goguenheim, J.; Gaxiola, G. (Facultad de Ciencias Biologicas, 2008)
The bacterial “floc” is a very complex ecosystem that works in a multifactor context where each parameter needs tobe considered. The bacterial microflora played initially the major role; it could stand on a unique role in totaldarkness. However, outdoors tanks getting larger and larger dimension induced an additional factor with the presenceof phytoplankton. At start, a few programs were held in order to comprehend how such a “black box” wouldfunction, some people speaking of an “external rumen”. Implication are coming from different fields such as theevolution of each bacteria communities in the medium, feed composition, management of wastes, sizing for acommercial operation. How shrimp performed in such environment? How shrimp could derive so many nutrients forits growth; would such a culture system be explained through a model? .First very positive results came from a zootechnical approach with considerable improvement in weight gain, healthyanimals at harvest compared to regular earthen ponds production; and recently it was evidenced a potential forreproduction of Litopenaeus stylirostris.That is the purpose of this paper to present a comprehensive approach of the use of “floc” ecosystem in a tankstructure called also “moulinettes”. Today there is such a great attention from farmers willing to go into intensive orsuper-intensive culture system that a comprehension of the trophic chain is necessary. Finally, there are greatexpectations for a biosecurity aspect with the disappearance of diseases outbreaks, the possibility to develop cultureout of the constraints of the seashore and overall an application of the concept of sustainability linked with aprofitable operation.